Sensitivity of heart rate and blood pressure to spontaneous activity in transgenic rats - Waterhouse, James M.; Witte, Klaus; Huser, Lutz; Nevill, A.; Atkinson, G.; Reilly, T.; Lemmer, Björn (Biological rhythm research, 2000)
Spontaneous changes in heart rate (HR), activity and systolic (SBP) and diastolic (DBP) blood pressure have been measured in 3 groups of 7 transgenic [TGR(mRen-2)27] rats for 4 weeks, starting at 12 weeks of age, and living on a 12:12 L:D schedule (light on at 07:00 h). Group TG-ENA was given enalapril, an angiotensin-converting enzyme inhibitor, in its drinking water; group TG-AMLO was given the calcium-channel blocker, amlodipine, by the same route; and group TG-VEH had no addition to its drinking water and so acted as a control. The sensitivity of the cardiovascular variables (CV's) to spontaneous activity was assessed throughout the study period by measuring the gradient of [CV / activity]. For the control (TG-VEH) group, mean HR was highest during the dark phase, at which time the sensitivity to spontaneous activity was least. By contrast, the circadian rhythms of SBP and DBP were inverted, peaking in the light (resting) phase, and there was no reliable difference between the light and dark phases with regard to the sensitivity of SBP or DBP to the effects of spontaneous activity. Enalapril reduced SBP and DBP, but did not alter their phase inversion with respect to HR. However, in SBP and DBP, as well as HR, sensitivities to spontaneous activity were now greater in the light phase. Amlodipine also reduced SBP and DBP and, in addition, greatly reduced the amplitude of their circadian rhythms. With this treatment also, sensitivity to spontaneous activity was greatest in the light phase for HR, SBP and DBP. A simple explanation of these results is that, in the absence of treatment, transgenic rats of this age have DBP and, particularly, SBP values that are too high in the light (resting) phase to permit much further rise due to spontaneous activity, and that this "ceiling effect" no longer holds if SBP and DBP have been reduced pharmacologically.
Published online: 09 Aug 2010
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 14.04.2022